PENGARUH MODAL DAN VOLUME PENJUALAN TERHADAP PENDAPATAN PEDAGANG DI PASAR BANYUASRI - Firmantara Lete, Maharta (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
This study aims to determine the effect of Capital and Sales Volume on the Income of Traders in the Banyuasri Market. The data collection technique used in this study was in the form of a questionnaire with a Likert Scale measuring instrument, where 80 respondents were selected as electronic money users. The data analysis technique used in this study is the Multiple Linear Regression Model, which is know as SPSS Statistic. The variables used in this research are Capital and Sales Volume. The results of this study indicate that the capital has a positive and significant with the result (4.024) with a t-count value that is greater than the t-table (1.989). Sales volume has a positive and significant with the result (3.898) with a t-count value that is greater than the t-table (1.989). And capital has a positive and significant on the sales volume with the result (6.276) with a t-count value that is greater than the t-table (1.989).